2011
DOI: 10.1128/jvi.00568-11
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Old World Hantaviruses Infect Renal Glomerular and Tubular Cells and Induce Disassembling of Cell-to-Cell Contacts

Abstract: Viral hemorrhagic fevers are characterized by enhanced permeability. One of the most affected target organs of hantavirus-induced hemorrhagic fever with renal syndrome is the kidney, and an infection often results in acute renal failure. To study the underlying cellular effects leading to kidney dysfunction, we infected human renal cell types in vitro that are critical for the barrier functions of the kidney, and we examined kidney biopsy specimens obtained from hantavirus-infected patients. We analyzed the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 84 publications
1
80
0
Order By: Relevance
“…RNA viruses such as vesicular stomatitis virus, influenza virus and rotavirus have been shown to influence the permeability barrier functions of epithelial cells with or without cytopathic effects at later stages of infection [54], [55]. Kidney biopsies from patients infected with highly pathogenic hantaviruses revealed altered expression and localization of ZO-1 which correlated with disease severity [56]. In many cases, viral proteins responsible for affecting TJ functions have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…RNA viruses such as vesicular stomatitis virus, influenza virus and rotavirus have been shown to influence the permeability barrier functions of epithelial cells with or without cytopathic effects at later stages of infection [54], [55]. Kidney biopsies from patients infected with highly pathogenic hantaviruses revealed altered expression and localization of ZO-1 which correlated with disease severity [56]. In many cases, viral proteins responsible for affecting TJ functions have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in the case of massive transient proteinuria, the associated glomerular lesions with respect to adhesion molecules, cytokines, and cell infiltration remain negligible [21] . The hantaviruses can infect not only vascular endothelial cells, but also glomerular endothelial cells, tubular cells, and podocytes, disrupting the cell-to-cell contacts in all of these cell types [42] . Indeed, in electron microscopic studies, fusion of podocyte foot processes was already found in 1978 [43,44] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, HCV infection promotes expression of vascular endothelial growth factor, which alters tight junction integrity and polarity of hepatocytes [89]. Hemorrhagic hantavirus infection of renal epithelial and endothelial cells results in redistribution and reduction in tight junction protein ZO-1 and reduced transepithelial electrical resistance [90]. Dengue virus infection increases vascular permeability, particularly in severe dengue hemorrhagic fever and dengue shock syndrome.…”
Section: Other Virus-tight Junction Interactions: Comparative Lessonsmentioning
confidence: 99%